Simbolisme Agama sebagai Protagonis dalam Film Horor - Melati Kusuma Wardhani, S.I.Kom, M.I.Kom, Melati Kusuma Wardhani, S.I.Kom, M.I.Kom (Profilm Jurnal Ilmiah Ilmu Perfilman dan Pertelevisian, 2024)
Several aspects show the changes taking place in the Indonesian horror film industry, and the correlation between changes at the international level and local phenomena is very clear. First, using local myths and legends as the basis of the story shows that the audience is drawn to content rooted in local traditions and culture. Secondly, technological advances around the world have led to improved visual quality and special effects in horror films. Third, production and distribution standards have been improved due to greater collaboration with the global film industry. As a result, Indonesian horror films have had a wider impact around the world. The methodological approach carried out in this study is called literature research. The results showed that in addition, the genre of horror films is changing by trying to include variations such as psychological, comedy, and supernatural horror to cater to different tastes of audiences. The narrative and message of the film also changed, with some Indonesian horror films incorporating social messages or social criticism, giving deep meaning to the horror story. In promoting Indonesian horror films, pop culture and social media play an important role as they allow producers to use viral trends, memes, and direct interaction with the audience. Overall, these transformations demonstrate the film producers' ability to adapt and be creative to technological and cultural transformations while maintaining a strong local cultural identity. As a result, Indonesia's horror film industry has become relevant and attractive to audiences at home and